HISTORY OF WATER-COLUMN ANOXIA IN THE BLACK SEA INDICATED BY PYRITE FRAMBOID SIZE DISTRIBUTIONS - Wilkin R.T.; Arthur M.A.; Dean W.E. (My University, 1997)
A detailed study of size distributions of framboidal pyrite in Holocene Black Sea sediments establishes the timing of a change from deposition under an oxic water column to deposition under an anoxic and sulfidic water column. In the most recent carbonate-rich sediments (Unit I) and in the organic carbon-rich sapropel (Unit II), framboid size distributions are remarkably uniform (mean diameter = 5 μm); over 95% of the framboids in Unit I and Unit II are < 7 μm in diameter. These properties of framboidal pyrite are consistent with framboid nucleation and growth within an anoxic and sulfidic water column, followed by transport to the sediment-water interface, cessation of pyrite growth due to the exhaustion of reactive iron, and subsequent burial. In contrast, the organic carbon-poor sediments of lacustrine Unit III contain pyrite framboids that are generally much larger in size (mean diameter = 10 μm). In Unit III, over 95% of the framboids are < 25 μm in diameter, 40% of framboids are between 7 μm and 25 μm, and framboids up to 50 μm in diameter are present. This distribution of sizes suggests framboid nucleation and growth within anoxic sediment porewaters. These new data on size distributions of framboidal pyrite confirm that the development of water-column anoxia in the Black Sea coincided with the initiation of deposition of laminated Unit II sapropels.
Keywords: BLACK SEA; ANAEROBIC ENVIRONMENT; FRAMBOIDAL TEXTURE; PYRITE; BLACK SHALE